Risk factors of arytenoid dislocation after endotracheal intubation: A propensity‐matched analysis. Issue 6 (24th November 2022) - Kong, Xiangyu; Song, Yang; Wang, Lijun; He, Guili; Ma, Changhong; Zhao, Rui; Wang, Minjun; Shi, Lin; Cui, Wanming
Abstract: Objective: Arytenoid dislocation (AD) after general anesthesia with endotracheal intubation (EI) is an iatrogenic injury that impairs patient function and requires reduction. We aimed to investigate the risk factors of AD following EI. Methods: This retrospective case‐control study involved surgical adults who received EI for general anesthesia at a single institution from June 2010 to June 2020. Cases included all the patients who had AD. We used a ratio of 1:5 to identify patients in the propensity‐matched control group. Results: Multivariate analysis of 49 cases with AD and 245 controls without AD demonstrated that the use of a nasogastric (NG) tube (odds ratio [OR], 23.9; 95% confidence interval [CI], 6.8–84.1), undergoing abdominal surgery (OR, 3.7; 95% CI, 1.2–11.9), and an operative time longer than 3 h (OR, 5.2; 95% CI, 2.1–12.9) were risk factors for AD. We did not find significant independent associations between AD and 40 years or older age, gender, body mass index, whether a laryngeal mask airway was used, endotracheal tube size, and EI performers' experience. Conclusion: The use of an NG tube, abdominal surgery, and longer operative time were risk factors for AD. Among these, the NG tube application showed a strong association with AD. Preventive measures of informing the patients of the increased risk and providing high‐level patient monitoring can reduce the incidence of AD. Level of Evidence: III Abstract : This propensity‐matched case‐control study investigated risk factors of arytenoid dislocation (AD) in surgical under general anesthesia using endotracheal intubation. Analysis of 49 patients with AD and 245 patients without AD showed that the use of a nasogastric tube, undergoing abdominal surgery, and longer operative time were risk factors for AD.